So we all have a basic idea of differentiating rules, for example; both of these hold true
\[y = Log_{e}{x} \Rightarrow \frac{dy}{dx} = \frac{1}{x}\]
y=ex⇒dxdy=ex
But why?
Well it doesn't take much to show both are true. Let's start with y=Logex
y=Logex
First let's use e to the power of both sides to get rid of that Loge
ey=x
Then use the chain rule and implicit differentiating to get
dxdy⋅ey=1
Rearrange to make dxdy the subject
dxdy=ey1
Substitute Logex for y
dxdy=eLogex1
Cancel the e and Loge to get
dxdy=x1
So that's that, but what about y=ex?
y=ex
First we'll use a natural Log on both sides
Logey=x
Then differentiate implicitly
dxdy⋅y1=1
Make dxdy the subject
dxdy=y
Substitute ex for y
dxdy=ex
That's those two taken care of.
What if we integrate Logex?
∫Logex
First we need to find a way to not integrate Logex. I know let's use integration by parts!
∫Logex⋅1
Good, let's make u=Logex and dxdv=1
We know:
∫udxdv=uv−∫vdxdu
So let's work it out then.
v=x
dxdu=x1
∫Logex=xLogex−∫1
∫Logex=xLogex−x+c
∫Logex=x(Logex−1)+c
That's all for now.
#Logarithms
#Differentiation
#Integration
#Naturallogarithm
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
There are no comments in this discussion.